Presentation: Antiquity and Actuality of Irrigation in the Andes (I) - Sherbondy, Jeanette (1986)
The two themes that stand out in this volume of Allpanchis are the analysis of technology within its socio-cultural context, and the incorporation of this analysis within a new policy for the development of the Andes. In pre-Hispanic times there was a wealth of complex and sophisticated technologies that are only recently being recognized: the dams, canals and cultivation under machaco en collo or tabla on the coast described by Antúnez de Mayolo; the irrigation systems in various areas of the sierra: on the western slope exposed by Gelles, in the Colca valley presented by Valderrama and Escalante and in the Inca Cusco described by Sherbondy; an underground drainage system in Inca Cusco that appears in Ardiles and the method for managing the lacustrine environments of the Altiplano by means of ridges or kurus present in Ramos's work.